Spatial Justice (s) and socio-environmental tensions: Challenges and possibilities for an ethnography of a transdisciplinary debate - Salamanca Villamizar, Carlos; Aztudillo Pizarro, Francisco (Instituto de Altos Estudios Sociales, 2016)
In this article we discuss some of the debates which address the concept of spatial justice in relation to contemporary ethnographies. First, we present a discussion about the multiple ways in which the different dimensions of spatial justice have been studied. Secondly, we highlight some of the main themes of research regarding the notion of spatial justice and the environment. Finally, we highlight some contributions and methodological challenges in relation to “ethnographic practices” identifying developments and limitations from a comparative perspective. Hence, we emphasize some of the aspects in which ethnography is responding to the challenges of the complex contemporary world in which space and society are interwoven.